Peningkatan Kompetensi Guru Agama Islam Berbasis E-Earning Melalui Supervisi Akademis Pengawas di MTs Binaan Kota Bengkulu Tahun Pelajaran 2022/2023 - M. Nuraini (UIN Fatmawati Sukarno Bengkulu, 2022)
This research is to describe the increased competency of e-learning-based Islamic religion teachers through the supervision of academic supervisors at Madrasah Tsanawiyah in Bengkulu City for the 2022/2023 academic year. Based on the analysis of the results of this study, it can be interpreted that the increase in the competency of Islamic religion teachers based on e-learning through the supervision of scholar supervisors at Madrasah Tsanawiyah in Bengkulu City shows that there is an increase in each cycle (cycle). Activities in coaching activities show that teachers can improve their competence in applying web-based models (E-Learning), well in every aspect. Improvement of teacher performance by supervisors through Academic Supervision shows an increase in each round. Teacher activities show that coaching activities through Academy Supervision are useful and can help improve teacher performance, to more easily understand the concept of the teacher’s role and function so that teacher performance can increase, as well as school capacity can be improved.